Comparison of textural and sensory characteristics of low‐fat mayonnaise prepared from octenyl succinic anhydride modified corn and white sorghum starches. Issue 1 (14th November 2014) - Ali, Tahira Mohsin; Waqar, Saad; Ali, Syeda; Mehboob, Sundus; Hasnain, Abid; Tester, Richard F.
<x xml:space="preserve">Abstract</x> Mayonnaise is a popular condiment containing 65–75% oil by weight. The aim of the study was to develop a low fat (75% fat‐replaced) mayonnaise using chemically modified octenyl‐succinic anhydride (OSA) corn and OSA‐sorghum starches. Secondly, the functional properties of native and modified corn and sorghum starches were also compared. The setback viscosity of OSA‐sorghum starch was found to be the least while the textural changes in OSA‐sorghum on cold storage were found to be negligible. Overall acceptability of low fat mayonnaise (LFM) was scored higher than full‐fat mayonnaise (FFM). But the textural attributes of LFM made from OSA‐sorghum were found to be quite similar to FFM.